2016
DOI: 10.1037/rep0000080
|View full text |Cite
|
Sign up to set email alerts
|

The intensive care unit experience: Psychological impact on family members of patients with and without traumatic brain injury.

Abstract: This study, to our knowledge, is the first of its kind to examine psychological differences in the ICU in those whose family members either have or do not have a TBI. Results suggest the TBI group endorsed more symptoms of depression and PTS symptoms at 3 months. Although it is unclear whether symptoms were directly related to the ICU experience or the injury itself, future research should explore the possible additive effect of postintensive care syndrome-family symptoms. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Eight studies identified that 15–57% of relatives reported the presence of PTSD symptoms at up to 6 months after the patients' discharge from ICU (McAdam et al ., ; Dithole and Thupayagale‐Tshweneagae, ; Sundararajan et al ., ; Andresen et al ., ; van den Born–van Zanten et al ., ; Warren et al ., ; Wintermann et al ., ; Wolters et al ., ). Significantly, Andresen et al .…”
Section: Health and Well‐beingmentioning
confidence: 97%
See 1 more Smart Citation
“…Eight studies identified that 15–57% of relatives reported the presence of PTSD symptoms at up to 6 months after the patients' discharge from ICU (McAdam et al ., ; Dithole and Thupayagale‐Tshweneagae, ; Sundararajan et al ., ; Andresen et al ., ; van den Born–van Zanten et al ., ; Warren et al ., ; Wintermann et al ., ; Wolters et al ., ). Significantly, Andresen et al .…”
Section: Health and Well‐beingmentioning
confidence: 97%
“…Thirteen studies reported moderate to severe depressive symptoms in 20–43% of relatives 2 to 3 months after ICU discharge (Van Pelt et al ., ; Douglas et al ., ; Lemiale et al ., ; Choi et al ., ; McAdam et al ., ; Hwang et al ., ; Sundararajan et al ., ; Andresen et al ., ; Gallop et al ., ; Cameron et al ., ; McPeake et al ., ; Warren et al ., ). Cameron et al .…”
Section: Health and Well‐beingmentioning
confidence: 99%
“…Other studies found an association between a greater severity of the disease [39], more days of hospitalization [40], persistent patient's pain [49], and the levels of PTSD symptoms. Another study on 82 family members of ICU patients found that being caregivers of ICU patients with a traumatic brain injury (TBI), rather than of ICU patients without TBI, was a risk factor for experiencing more PTSD symptoms [57]. Furthermore, Dew et al [47] examined 190 family caregivers to heart transplant recipients and found that in the first year post-transplant, caregivers presented higher PTSD symptoms.…”
Section: Risk Factors For Ptsdmentioning
confidence: 99%
“…Many family members find traumatic injury and subsequent hospitalization of a loved one to be jarring and overwhelming. Family members of patients are likely to contend with symptoms of depression, post-traumatic stress, anxiety, and grief during the acute phase post-injury (Warren, Rainey, Weddle, et al, 2016;Davidson, Jones, & Bienvenu, 2012). Family members, in their effort to support their loved one, will often remain at bedside or nearby within the hospital for many hours each day.…”
Section: Early Inpatient Psychological Interventionmentioning
confidence: 99%